2022
DOI: 10.1029/2022ja030276
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Local Time and Latitude Distribution of Ionospheric Large‐Spatial‐Scale EMIC Wave Events: Swarm Observations

Abstract: In the present work, the magnetic local time and latitude (MLT and MLat) distributions of ionospheric large‐spatial‐scale (>20° MLat) electromagnetic ion cyclotron waves were investigated using high‐resolution 50‐Hz geomagnetic field data from Swarm A and B satellites. Both parallel and transverse waves were studied in a comparative manner for different geomagnetic activities and seasons. Frequent occurrences of large‐spatial‐scale waves in the South Atlantic Anomaly and North America, where the parallel waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In a number of publications authors relate Pc1 oscillations, observed by LEO satellites, to EMIC waves (e.g., Kim et al., 2020, 2021; Wang, He, & Lühr 2022; Wang, Sun, et al., 2022; Wang et al., 2019, 2021). All of their results are based on single‐satellite recordings, which do not allow to resolve the spatial/temporal ambiguity.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a number of publications authors relate Pc1 oscillations, observed by LEO satellites, to EMIC waves (e.g., Kim et al., 2020, 2021; Wang, He, & Lühr 2022; Wang, Sun, et al., 2022; Wang et al., 2019, 2021). All of their results are based on single‐satellite recordings, which do not allow to resolve the spatial/temporal ambiguity.…”
Section: Observationsmentioning
confidence: 99%
“…We investigated further published EMIC events such as the one on 29 March 2015 from Wang, Sun, et al. (2022). From the spectrogram in Figure 12 wave activity around 1 Hz can be seen in the northern and southern hemispheres.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As ducted Pc1 waves can be attenuated, their sustainability (or travel distance) depends on the amplitude of the incident transverse wave and the structure of the ionospheric plasma which plays a major role in the transmission of Pc1 waves. Ducted Pc1 waves can transfer thousands of kilometers through the ionospheric waveguide, and they are observed by magnetometers on both ground and low Earth orbit satellites over a wide latitudinal range (Kawamura et al., 1981; Kim, Shiokawa, Park, Miyoshi, Miyashita, et al., 2021; Kim et al., 2010, 2011, 2018, 2020; Pisa et al., 2015; Wang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is worth studying whether ducting can expand from the auroral oval into the polar cap when the plasma density is sufficient. Also, (b) previous studies just addressed 1‐dimensional features of ionospheric ducting along the satellite track (e.g., Wang et al., 2022) or magnetic meridian on the ground (e.g., Kim et al., 2010). Although a theoretical study predicted that the ducting is most efficient in the magnetic meridian (Greifinger & Greifinger, 1973), this expectation has not yet been thoroughly tested observationally.…”
Section: Introductionmentioning
confidence: 99%